Piil Pesenggiri Team Work Learning Model for Collaborative Problem-Solving Skills of Junior High School Students - Friska Octavia Rosa; Arif Rahman Aththibby; Dya Qurotul A’yun (Postgraduate, University of Mataram, 2023)
Collaborative problem-solving is one of the essential concerns in the learning process to prepare human resources who ready to compete in the future. This study is aimed to inspect the impact of the Piil Pesenggiri Team Work Learning (PPTWL) model implementation in Science classes of Junior High schools. This study was a pre-experimental research conducted without involving the control class, namely one-group pretest posttest design. Collaborative problem solving skills are students' abilities to engage in cognitive and social processes effectively, attempting to solve encountered problems, in groups. Collaborative problem solving observation sheet was the instrument used for the study. Study results indicate that PPTWL model is effective to be used in improving collaborative problem-solving skills of students in science-related materials. In-depth studies on learning cultures and materials and repetitive model application are required to obtain more accurate outcomes in future studies.